Efficient synthesis of ethyl 2-(oxazolin-2-yl)alkanoates via ethoxycarbonylketene-induced electrophilic ring expansion of aziridines - Lei, Yelong; Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2022)
Alkyl 2-diazo-3-oxoalkanoates generate alkoxycarbonylketenes, which undergo an electrophilic ring expansion with aziridines to afford alkyl 2-(oxazolin-2-yl)alkanoates in good to excellent yields under microwave heating. The method is a convenient and clean reaction without any activators and catalysts and can be also applied in the synthesis of 2-(oxazolin-2-yl)alkanamides and 1-(oxazolin-2-yl)alkylphosphonates.
Keywords: aziridine; diazooxoester; diazo compound; ketene; oxazoline; ring expansion

(untitled) - Tilvi, S.; Singh, K. S. (Curr. Org. Chem., 2016)

(untitled) - Davyt, D.; Serra, G. (Mar. Drugs, 2010)

(untitled) - Bansal, S.; Halve, A. K. (Int. J. Pharm. Sci. Res., 2014)

(untitled) - Nicolaou, K. C.; Lizos, D. E.; Kim, D. W.; Schlawe, D.; de Noronha, R. G.; Longbottom, D. A.; Rodriquez, M.; Bucci, M.; Cirino, G. (J. Am. Chem. Soc., 2006)

(untitled) - Tsuda, M.; Yamakawa, M.; Oka, S.; Tanaka, Y.; Hoshino, Y.; Mikami, Y.; Sato, A.; Fujiwara, H.; Ohizumi, Y.; Kobayashi, J. (J. Nat. Prod., 2005)

(untitled) - Degnan, B. M.; Hawkins, C. J.; Lavin, M. F.; McCaffrey, E. J.; Parry, D. L.; Watters, D. J. (J. Med. Chem., 1989)

(untitled) - Connon, R.; Roche, B.; Rokade, B. V.; Guiry, P. J. (Chem. Rev., 2021)

(untitled) - Xu, J.; Ma, L.; Jiao, P. (Chem. Commun., 2004)

(untitled) - Ma, L.; Jiao, P.; Zhang, Q.; Xu, J. (Tetrahedron: Asymmetry, 2005)

(untitled) - Ma, L.; Du, D.-M.; Xu, J. (J. Org. Chem., 2005)

(untitled) - Wipf, P. (Chem. Rev., 1995)

(untitled) - Gaumont, A.-C.; Gulea, M.; Levillain, J. (Chem. Rev., 2009)

(untitled) - Katritzky, A. R.; Cai, C.; Suzuki, K.; Singh, S. K. (J. Org. Chem., 2004)

(untitled) - Mohammadpoor-Baltork, I.; Moghadam, M.; Tangestaninejad, S.; Mirkhani, V.; Hojati, S. F. (Catal. Commun., 2008)

(untitled) - Li, X.; Zhou, B.; Zhang, J.; She, M.; An, S.; Ge, H.; Li, C.; Yin, B.; Li, J.; Shi, Z. (Eur. J. Org. Chem., 2012)

(untitled) - Schwekendiek, K.; Glorius, F. (Synthesis, 2006)

(untitled) - Morse, P. D.; Nicewicz, D. A. (Chem. Sci., 2015)
And cited therein.

(untitled) - Minakata, S.; Morino, Y.; Ide, T.; Oderaotoshi, Y.; Komatsu, M. (Chem. Commun., 2007)

(untitled) - Hajra, S.; Bar, S.; Sinha, D.; Maji, B. (J. Org. Chem., 2008)

(untitled) - Chen, X.; Lin, C.; Du, H.; Xu, J. (Adv. Synth. Catal., 2019)

(untitled) - Chen, X.; Huang, Z.; Xu, J. (Adv. Synth. Catal., 2021)

(untitled) - Chen, X.; Lei, Y.; Fu, D.; Xu, J. (Org. Biomol. Chem., 2021)

(untitled) - Li, S.; Chen, X.; Xu, J. (Tetrahedron, 2018)

(untitled) - Wang, X.; Zhang, J.; He, Y.; Chen, D.; Wang, C.; Yang, F.; Wang, W.; Ma, Y.; Szostak, M. (Org. Lett., 2020)

(untitled) - Xie, Y.; Chen, X.; Liu, X.; Su, S.-J.; Li, J.; Zeng, W. (Chem. Commun., 2016)

(untitled) - Erhunmwunse, M. O.; Steel, P. G. (J. Org. Chem., 2008)

(untitled) - Lv, H.; Shi, J.; Wu, B.; Guo, Y.; Huang, J.; Yi, W. (Org. Biomol. Chem., 2017)

(untitled) - Ciszewski, Ł. W.; Durka, J.; Gryko, D. (Org. Lett., 2019)

(untitled) - Eckelbarger, J. D.; Wilmot, J. T.; Epperson, M. T.; Thakur, C. S.; Shum, D.; Antczak, C.; Tarassishin, L.; Djaballah, H.; Gin, D. Y. (Chem. – Eur. J., 2008)